A study to determine the utilization of physiotherapy services after lower limb amputation at the UTH, Zambia Italian Orthopedic Hospital and Chainama Hills Hospital - Silungwe, Leonard M. (Lusaka: University of Zambia , School of Medicine, 2011)
In the advent of road traffic accidents, diabetes mellitus and malignancies, lower extremity amputation has been one of the preferred surgical procedures done in Zambia to prevent secondary complications. Therefor referall to physiotherapy following post surgery is ideal to enhance patient recovery and general good health. The study title is to determine the utilisation of physiotherapy services after lower limb amputation at the UTH, Zambia Italian Orthopedic Hospital and Chainama Hills Hospital.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Physiotherapy.
Includes bibliographical references.
Keywords: Amputees--Rehabilitation.